Perception of doctor-patient relationship in the present time from the viewpoint of doctors: A qualitative study at a tertiary health-care center in Eastern India - Barun Kumar; Uttam Kumar Paul; Dilip Kumar Pal (Wolters Kluwer Medknow Publications, 2020)
Context: Doctor-patient relationship has gone through some troubled times in the recent past. Quality data regarding this is lacking in the Indian setting. Aims: The study aim was to find the perception of doctors regarding doctor-patient relationship. Settings and Design: The study was conducted at a tertiary health-care center in West Bengal. It was a qualitative study including in-depth interviews and focus group discussions (FGDs). Subjects and Methods: The study comprised of in-depth interviews (IDI) of thirty residents and three FGDs, involving 33 residents. Statistical Analysis Used: Data analysis was performed manually by deductive approach. Descriptive "codes" of the text information were done. The consolidated criteria for reporting qualitative research guidelines were followed. Results: Doctor-patient relationship was perceived as of mutual trust and respect. Overburdened doctors, impatient patients, unrealistic expectations from the treatment, and lack of infrastructure were some of the agreed-upon factors for the strained relationship. A combined corrective effort is needed to salvage the current situation. Conclusions: A healthy doctor-patient relationship is instrumental in the holistic picture of health care. Doctors, patients, administration, and media have shared causation to the problem and have equal responsibility for its amendment.